Does Rohu (Labeo rohita) (F. Hamilton, 1822) have different forms of Immunoglobulins? - Suresh Babu, P. P.; Shankar, K. M.; Honnananda, B. R.; Abhiman, P. B. (Fishery Technology, 2017)
Characterisation of immunoglobulin (Ig) is an essential prerequisite for development of anti- fish Ig antibody. There are number of reports describing the characteristics of rohu Ig which state the existence of different forms of antibodies in rohu. The present review is an attempt to compile these reports for analyzing the probable reason for the existence of such forms and the possible future research requirements for confirming the same.